PELATIHAN PEMBUATAN PETA DIGITAL BERBASIS SISTEM INFORMASI GEOGRAFIS DI DESA REJOSO - Dewi Retno Sari Saputro; Ririn Setiyowati; Purnami Widyaningsih (Politeknik Negeri Sriwijaya, 2021)
The Rejoso Village Government is the smallest part of the government structure in Jogonalan District, Klaten Regency. The village information system is currently still in the form of a manual information system where services are carried out by officers with a complicated and slow service system. Therefore, the solution to this problem is the need for an inventory of spatial data as a form of village information system. Village data and information can be presented visually in the form of digital maps and packaged in a geospatial-based village information system by utilizing a geographic information system (GIS). Training on making GIS-based digital maps using QGIS software was carried out to develop the competence of village officials and youth organizations in overcoming these problems.